Under the trapdoor - resolving the taxonomy and phylogeography of the trapdoor spider genus Stasimopus (Mygalomorphae: Stasimopidae) of the Karoo - Sole, Catherine L. (University of Pretoria, 2023)
Thesis (PhD (Zoology))--University of Pretoria, 2023.